Shared-use rail corridors: a comparison of institutional perspectives in the United States and the European Union. Issue 3 (4th May 2022) - Minn, Michael; Brady, Sylvia; Cidell, Julie; Ratner, Keith; Goetz, Andrew
ABSTRACT: This paper reviews existing literature to identify issues, challenges, and best practices associated with shared-use freight and passenger rail corridors. Specifically, this paper will compare and contrast shared-corridor practices from an institutional perspective in the United States and the European Union. These two regions were chosen because of their shared social, political, technological, and economic ties, their historical mixes of private and state railroad operations, and because of the significant contemporary differences in the role of rail in these two regions. That mix of similarities and differences clarifies important commonalities specific to freight and passenger railroads that may be applicable in other times and places. Best practices include planning for: capital investment, long-term time horizons, measurable incremental improvements, regional multi-modality, and mutual benefits between freight and passenger operations.